Quality of the materials and methods section of original dental research articles published in the iranian and international journals - Soroush Malek Afzali; Sedigheh Bakhtiari; Elaheh Moghym Farougi (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: Lack of scientific writing skills is believed to be a major obstacle in the course of research publication and dissemination by the Iranian researchers. Without following the globally accepted publication standards, dissertations, and projects cannot reach their final goal of being published and incorporated into practice. We aimed to compare the writing quality of a number of dental original articles written in Farsi and published in the Iranian journals with those written in English and published in international journals. Materials and Methods: In this analytical cross-sectional study, we selected 64 articles from six dental journals (three international English journals and three Farsi journals) by simple random sampling method. A list of 48 variables covering the study design, sampling method, subject allocation, ethical issues, interventions, measurements, and statistical methods was used to evaluate each article. The results were analyzed using Chi-square or Fisher's exact test. Results: Our results demonstrated that Farsi articles (n = 32) fulfilled 61.1% of our checklist criteria while English articles (n = 32) achieved a score of 59.1%, with no statistically significant difference (P > 0.05). Conclusion: We believe that the selected articles successfully reported most of the necessary elements. Their main shortcoming seemed to be the lack of clarification of details.